Development of a Perception Scale of Private Lesson: A Validity and Reliability Study - Ahmet Yildiz; Mesut Butun; Ali Turkdogan; Ekrem Kocak (Mimbar Sekolah Dasar, 2022)
The purpose of the research is to develop a valid and reliable perception scale that can measure the perception of math teachers (198) and science teachers (120) towards private lesson. In the validity studies, the exploratory factor analysis was made with the SPSS 25.0 package program after that the confirmatory factor analysis was made with Lisrel 8.71 software. To develop the scale; 1. Creation of Item Pool 2. Obtaining Expert Opinion, 3. Creation of Pre-Trial Form 4. Factor Analysis 5. Confirmatory factor analysis. According to factor analysis; Kaiser Meyer Olkin (KMO) rate; .780; Bartlett test result: 7466.539; Cronbach alpha reliability coefficient is: .901. According to confirmatory factor analysis: Root Mean Square Error of Approximation (RMSEA) 0.043 (.05); p-Value for Test of Close Fit .00 (.05, Goodness of Fit Index (GFI) .96, Adjusted Goodness of Fit Index (AGFI) .93; Normed Fit Index (NFI) .97; Relative Fit Index (RFI) .96; Incremental Fix Index (IFI): .99; Degrees of Freedom: 38; Root Mean Square Residual (RMR): .037 and NonNormed Fit Index (NNFI): .98. According to research findings, the perception scale is valid and reliable so it can be used to determine math teachers and science teachers’ positive and negative perceptions of private lesson.